2017
DOI: 10.1038/srep46679
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK blockade decreases atherosclerotic lesion size and progression through suppression of STAT1 signaling in diabetic mice

Abstract: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK/Tnfsf12) is a cytokine implicated in different steps associated with vascular remodeling. However, the role of TWEAK under hyperglycemic conditions is currently unknown. Using two different approaches, genetic deletion of Tnfsf12 and treatment with a TWEAK blocking mAb, we have analyzed the effect of TWEAK inhibition on atherosclerotic plaque progression and stability in streptozotocin-induced diabetic ApoE deficient mice. Genetic inactivation of Tnfs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…In this sense, treatment of SMCs with rTWEAK favors the vascular phenotypic switching, increasing osteopontin and decreasing α -actin and calponin gene expression. Moreover, the number of osteopontin positive SMCs increases in atherosclerotic plaques from TWEAK/ Apolipoprotein E (ApoE) double deficient mice, confirming the role of TWEAK on SMCs phenotypic changes in vivo [39]. Both, inflammatory cells and SMCs favor plaque progression by increasing cytokines and MMPs expression.…”
Section: Lesion Progressionmentioning
confidence: 68%
See 3 more Smart Citations
“…In this sense, treatment of SMCs with rTWEAK favors the vascular phenotypic switching, increasing osteopontin and decreasing α -actin and calponin gene expression. Moreover, the number of osteopontin positive SMCs increases in atherosclerotic plaques from TWEAK/ Apolipoprotein E (ApoE) double deficient mice, confirming the role of TWEAK on SMCs phenotypic changes in vivo [39]. Both, inflammatory cells and SMCs favor plaque progression by increasing cytokines and MMPs expression.…”
Section: Lesion Progressionmentioning
confidence: 68%
“…This trimeric structure induces the recruitment of TRAF2 and TRAF5 though the TRAF-binding motif (PIEET) in the cytoplasmic tail, and leads the activation of different signaling pathways [14,35]. TWEAK-Fn14 binding activates several signal transduction pathways that implicate both canonical and non-canonical NF-kB pathways [14,36], mitogen-activated protein kinases pathway (MAPK) [37], PI3K/AKT [38], JAK/STAT signaling pathway [39,40], and transforming growth factor-β-activated kinase 1 [41]. MAPK activation induced by recombinant soluble TWEAK (rTWEAK) has been reported in endothelial cells [33], Thp-1 monocytic cell line [26], and cardiomyocytes [30].…”
Section: Signaling Pathways Activated By Tweak-fn14 Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…STAT1 is a member of the STATs protein family and is composed of seven potential cytoplasmic transcription factors that play key roles in different physiological functions including apoptosis, cell survival, immune response, and proliferation [18]. It has been demonstrated that TWEAK induces proinflammatory genes mRNA expression through its receptor Fn14 and STAT1 activation in cultured vascular smooth muscle cells [19]. Researches have shown that LncRNA H19 contributes to hippocampal glial cell activation via JAK/STAT signaling in a rat model of temporal lobe epilepsy [20].…”
Section: Introductionmentioning
confidence: 99%